Polyphyllin II induced apoptosis of NSCLC cells by inhibiting autophagy through the mTOR pathway - Yuhan Jiao; Ming Xin; Juanjuan Xu; Xindong Xiang; Xuan Li; Jingjing Jiang; Xiuqin Jia (Taylor & Francis Group, 2022)
Context Polyphyllin II (PPII) is a steroidal saponin isolated from Rhizoma Paridis. It exhibits significant antitumor activity such as anti-proliferation and pro-apoptosis in lung cancer.Objective To explore whether PPII induce autophagy and the relationship between autophagy and apoptosis in non-small cell lung cancer (NSCLC) cells.Materials and methods The effects of PPII (0, 1, 5, and 10 μM) were elucidated by CCK8 assay, colony formation test, TUNEL staining, MDC method, and mRFP-GFP-LC3 lentivirus transfection in A549 and H1299 cells for 24 h. DMSO-treated cells were selected as control. The protein expression of autophagy (LC3-II, p62), apoptosis (Bcl-2, Bax, caspase-3) and p-mTOR was detected by Western blotting. We explored the relationship between autophagy and apoptosis by autophagy inhibitor CQ (10 μM) and 3-MA (5 mM).Results PPII (0, 1, 5, and 10 μM) inhibited the proliferation and induced apoptosis. The IC50 values of A549 and H1299 cells were 8.26 ± 0.03 and 2.86 ± 0.83 μM. We found that PPII could induce autophagy. PPII promoted the formation of autophagosome, increased the expression of LC3-II/LC3-I (p < 0.05), while decreased p62 and p-mTOR (p < 0.05). Additionally, the co-treatment with autophagy inhibitors promoted the protein expression of c-caspase-3 and rate of Bax/Bcl-2 (p < 0.05), compared with PPII-only treatment group. Therefore, our results indicated that PPII-induced autophagy may be a mechanism to promote cell survival, although it can also induce apoptosis.Conclusions PPII-induced apoptosis exerts its anticancer activity by inhibiting autophagy, which will hopefully provide a prospective compound for NSCLC treatment.